Identification and genome insights into Pyrenochaeta nobilis, a novel endophytic fungus isolated from Astragalus membranaceus with gray mold-control activity - Yang, Fan; Wang, Shuang; Jiang, Xifeng; Du, Hongrui; Liu, Yu; Zhou, Yuanyuan; Liu, Chunlai (Frontiers in Plant Science, 2025)
IntroductionGray mold, caused by the necrotrophic fungus Botrytis cinerea, is a significant threat to agricultural production, especially under low temperature and high humidity conditions. This disease can cause substantial yield losses in various crops, including tomatoes. To address this issue, the search for novel biocontrol agents has become a priority. In this study, we explored the potential of endophytic fungi isolated from wild medicinal plants in the southern foothills of the Daxing’an Mountains in China as biocontrol resources against B. cinerea.MethodsEndophytic fungi were isolated from the roots of Astragalus membranaceus, a wild medicinal plant native to the study area. Among the isolates, Pyrenochaeta nobilis strain SFJ12-R-5 (CGMCC No.17766) was selected for its significant antagonistic activity against B. cinerea. The inhibitory effects of P. nobilis on B. cinerea were evaluated through in vitro assays, including mycelial growth inhibition tests and lesion inhibition tests on tomato leaves and fruits. Additionally, the genome of P. nobilis SFJ12-R-5 was sequenced using a combination of next-generation and third-generation sequencing techniques, followed by systematic annotation and identification of key gene families, such as carbohydrate-active enzymes (CAZymes) and phage-related (Phi) genes.ResultsP. nobilis strain SFJ12-R-5 exhibited strong inhibitory effects on B. cinerea, with a mycelial growth inhibition rate of 66.67 ± 3.15% and a large inhibition zone of 20.83 ± 3.78 mm. The fresh fermentation filtrate of P. nobilis, even at a 10-fold dilution, completely inhibited the growth of pathogenic hyphae. In vitro tests on tomato leaves and fruits showed lesion inhibition rates of 87.21% and 100%, respectively. Furthermore, plants co-treated with B. cinerea and the P. nobilis filtrate had a significantly lower gray mold disease severity (28.57%) compared to those inoculated solely with B. cinerea (75.34%), indicating a disease reduction rate of 62.08%. The genome of P. nobilis SFJ12-R-5 was successfully assembled and annotated, revealing the presence of CAZymes and Phi genes that may contribute to its biocontrol potential.DiscussionOur findings provide the first evidence that P. nobilis could serve as a promising natural antagonist against B. cinerea, particularly in integrated disease management systems for tomato production in greenhouses. The high-quality genome sequence and the identification of key gene families lay a solid foundation for future research on the molecular mechanisms underlying the inhibitory activity of Pyrenochaeta spp. against B. cinerea. Further studies are needed to explore the practical application of P. nobilis in agricultural settings and to elucidate its mode of action at the molecular level.